Analisis investasi sektor industri manufaktur, pengaruhnya terhadap pertumbuhan ekonomi dan penyerapan tenaga kerja di Indonesia - Irma Mar'atus Sholihah; Syaparuddin Syaparuddin; Nurhayani Nurhayani (Jurnal Paradigma Ekonomika, 2017)
This resource conducted to analyze the factors that influence investment in the manufacturing industry in Indonesia, analyze influence of investment the manufacturing industry to economic growth and employment of manufacturing in Indonesia. This resource uses approach of simultaneous with two stage square method (2SLS). The result shows that investment in the manufacturing industry simultaneously influenced by interest rate, exchange rate, and manufacturing industry employment. That infestation used as one of component of economic development an area because through investment, production capacity can be improved, then can be improved the output, which will eventually increase the economic growth and the manufacturing industry employment in Indonesia.